Representation of Men in the Film “Sore: Istri dari Masa Depan”: A Roland Barthes Semiotic Analysis - Sinta Yus Libu Putri; Nina Queena Hadi Putri (MASI Mandiri Edukasi, 2026)
The film Sore: Istri dari Masa Depan (2025) presents a representation of masculinity that differs from the dominant patterns commonly found in mainstream Indonesian cinema. The male protagonist, Jonathan, is not portrayed as a stable, heroic, or authoritative figure, but rather as a vulnerable individual experiencing an identity crisis and in need of self-reflection to achieve independence. This study analyses how Jonathan’s masculinity is constructed through visual and narrative signs in the film, using Roland Barthes’ semiotic approach. The research employs a qualitative method with a descriptive-analytical design. Primary data were obtained through close viewing of scenes, dialogues, gestures, and visual elements in the film, while secondary data were collected from relevant literature on semiotics, film studies, and masculinity studies. The analysis applies Barthes’ three levels of meaning denotation, connotation, and myth, and is further enriched by R.W. Connell’s perspective on hegemonic masculinity. The findings indicate that the film deconstructs the myth of hegemonic masculinity that emphasises absolute independence, emotional control, and dominance, and instead offers an alternative masculinity that values vulnerability, self-awareness, and a commitment to a healthy lifestyle as new forms of strength. Thus, Sore: Istri dari Masa Depan not only represents individual transformation but also reflects a broader shift in the discourse on masculinity within contemporary Indonesian socio-cultural contexts.